In vitro biomechanical comparison of limited contact dynamic compression plate and locking compression plate - Aguila, A. Z.; Manos, J. M.; Orlansky, A. S.; Todhunter, R. J.; Trotter, E. J.; van der Meulen, M. C. H. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The locking compression plate (LCP) supports biological osteosynthesis by functioning as an internal fixator, rather than as a full or limited contact bone plate which must be adequately contoured and affixed directly to the bone for stable internal fixation of the fracture. In order to help justify the use of the LCP in our veterinary patients, in vitro biomechanical testing was performed comparing the LCP to the conventional limited contact dynamic compression plate (LC-DCP) in canine femurs. We hypothesized that the LCP construct would be at least as stiff under bending and torsional loads as the LC-DCP. The LCP and LC-DCP were applied over a 20-mm osteotomy gap to contralateral bones within each pair of 14 femora. Non-destructive four-point bending and torsion, and cyclical testing in torsion were performed. The constructs were then loaded to failure in torsion. In medial-lateral and lateral-medial structural bending, significant differences were not found between the LCP and LC-DCP, however, at the gap, the LCP construct was stiffer than the LC-DCP in lateral-medial bending. Significant differences in behaviour over time were not noted between the plate designs during cyclical testing. When loading the constructs to failure in internal rotation, the LC-DCP failed at a significantly lower twist angle (P = .0024) than the LCP. Based on the similar performance with loading, the locking compression plate is a good alternative implant for unstable diaphyseal femoral fracture repair in dogs.
Keywords: Mechanical testing; LCP; LC-DCP